Defined domains and cleavage determine the diverse functions of piscine myocarditis virus p33 protein - Amono, Racheal; Fredlund, Snøa A. T. N.; Chesnais, Morgane; Thiede, Bernd; Markussen, Turhan; Evensen, Øystein; Mikalsen, Aase B. (Frontiers in Microbiology, 2025)
Piscine myocarditis virus (PMCV) causes chronic, necrotizing myocarditis in Atlantic salmon. Originally, PMCV was identified based on its genetic homology and genomic organization, indicating a relationship to viruses of the Ghabrivirales order, specifically the former Totiviridae family, whose members predominantly infect fungi or protozoans and lack an extracellular life cycle stage. However, PMCV was the first virus of this order found to infect a vertebrate host. Since then, other piscine viruses and viruses infecting terrestrial and aquatic arthropods have been described and recently assigned to new virus families within the order. PMCV is now classified in Pistolviridae. All these viruses infecting multicellular hosts encode proteins that are believed to be involved in extracellular transmission. In PMCV, this relates to a protein of size 33.4 kDa (p33) encoded by a unique third open reading frame. To investigate its characteristics and role, we expressed various recombinant variants of p33 in cultured cells. Our results demonstrate that p33 expression induces a cytotoxic phenotype in transfected cells. The full-length protein undergoes processing into smaller peptide variants. Previous in silico analysis predicted an N-terminal chemokine-like domain, and our present results show that this domain is secreted as peptides capable of inducing cytotoxicity when expressed alone. The C-terminal region includes sequence characteristics of a small hydrophobic domain, which appears crucial for the correct processing of the full-length protein into N- and C-terminal peptides and directing the C-terminal peptides to a high membrane concentration. Investigations into p33 function could elucidate how PMCV achieves extracellular transmission, a mechanism that may be conserved among viruses of Pistolviridae. The findings in this study provide evidence that p33 has structural and functional characteristics of a protein adapted to facilitate host cell membrane interaction and cell lysis, potentially enabling extracellular viral release. These insights may provide evolutionary evidence that pistolviruses have acquired the uncommon trait of viral transmission within the order Ghabrivirales, broadening our understanding of virus–host adaptation in vertebrates.